Electronics for Ultrasonic Imaging System - Svilainis, L.; Dumbrava, V.; Kitov, S.; Aleksandrovas, A.; Tervydis, P.; Liaukonis, D. (Elektronika ir Elektrotechnika, 2014)
Design of ultrasonic imaging system is presented. System has a modular structure with main acquisition and front end electronics separated in order to have minimal path for host PC connectivity and shortest path to ultrasonic transducer. Such acquisition modules placement allows reducing the induced EMI and increasing the flexibility of the system. Positioning module is also separate and allows various scanning equipment configurations. Evaluation of excitation and reception electronics parameters is presented. Essential measurement procedures outlined. Signal digitization parameters (sampling frequency, clock jitter and quantisation) were chosen to balance time of flight estimation random errors versus interpolation bias errors. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.8024